The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/echo.14140
|View full text |Cite
|
Sign up to set email alerts
|

Left atrium function and deformation in very preterm infants with and without volume load

Abstract: LA 2DSTE analysis is feasible in preterm infants and provides detailed information on atrium mechanics. Further studies are needed to explore the clinical value of these new parameters in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
4
16
0
Order By: Relevance
“…The median of the reported mean or median birth weight was 1,028 (range 797–1,259) g. The exact gestational ages and birth weights were not available for four studies ( 28 , 29 , 69 , 74 ). Seven of the 20 studies performed multiple cardiac ultrasounds to evaluate the PDA ( 21 , 24 , 25 , 27 , 67 , 72 , 73 ). The echocardiography was performed between 5 h and 28 days of postnatal age in all studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median of the reported mean or median birth weight was 1,028 (range 797–1,259) g. The exact gestational ages and birth weights were not available for four studies ( 28 , 29 , 69 , 74 ). Seven of the 20 studies performed multiple cardiac ultrasounds to evaluate the PDA ( 21 , 24 , 25 , 27 , 67 , 72 , 73 ). The echocardiography was performed between 5 h and 28 days of postnatal age in all studies.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty articles were included in group 2 (GA < 30 weeks and/or BW < 1,250 g) (11,(21)(22)(23)(24)(25)(26)(27)(28)(29)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76). The median of the reported mean or median GA of the 2,980 patients in group 2 was 28.0 (range 26.2-28.8).…”
Section: Subgroup Analysismentioning
confidence: 99%
“…A recent consensus document tried to standardize definitions and techniques for using LAS in adults. The same would be needed in neonates, given the fact that the current available data were obtained with different types of software and different modalities of both image acquisition and postprocessing analysis [ 8 , 9 , 10 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, few data on LAS are available in neonates and no data are available in the first days of life, also known as ‘transitional period’, when the transition from intrauterine to extrauterine circulation occurs [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been conflicting reports between LA function indices determined by strain imaging with 2D-STE in humans. A previous study enrolling infants with patent ductus arteriosus demonstrated that cardiac volume overload secondary to this disease was associated with the impairment of reservoir and booster pump functions evaluated with LA strains and SRs [4]. On the contrary, another previous study including healthy humans showed that the acute decrease in cardiac volume load caused by a tilt maneuver was associated with the impairment of reservoir, conduit, and booster pump functions assessed on the basis of LA strains [10].…”
Section: Discussionmentioning
confidence: 99%